Fracture Analysis of Functionally Graded Material (FGM) Plates Using Extended Finite Element Method: A Review. - Prasad A. Bojage; S.P. Palekar (International Journal of Fracture Mechanics and Damage Science, 2026)
Functionally Graded Materials (FGMs), have drawn a lot of interest in various engineering applications due to their superior mechanical properties and ability to withstand extreme conditions. Fracture analysis in FGMs focuses on understanding how cracks initiate and propagate within these complex materials. The stress distribution becomes irregular due to spatial property variations which produces different crack paths than what occurs in homogeneous materials. The examination of FGM plates under fracture conditions requires immediate research because it applies crucially to biomedicine together with automotive and aerospace industries. The true engineering world contains multiple unknowns regarding material properties and load conditions together with dimensional specifications. The uncertainties are evaluated through probabilistic fracture analysis to make precise predictions on FGM plate failure behaviours. This review focuses on analysing how XFEM determines fracture behaviours and propagating cracks in FGM plates. This study details advancements in XFEM technology and explains its implementation challenges when studying FGMs. XFEM performance needs testing against other numerical approaches for determining its accuracy in predicting fracture properties. The writer highlights the need for enhanced computer models as the final point in describing the research paths ahead. In addition to its theoretical significance, fracture modelling of FGM plates has substantial practical implications in the design of high-performance structural components. FGMs are typically characterized by a continuous gradation of material properties, such as Young’s modulus, thermal conductivity, and fracture toughness, often following exponential or power-law distributions. This gradation minimizes stress concentrations at interfaces and enhances resistance to thermal and mechanical loading. However, it also complicates crack-tip stress field evaluation, making conventional fracture mechanics approaches insufficient for accurate prediction.
Keywords: Functionally graded materials; Monte Carlo Simulation; XFEM; fracture mechanics; probabilistic analysis